Local positive feedback and the persistence and recovery of fringe Avicennia marina (Forssk.) Vierh. mangroves - Huisman, T.J; Langevelde, F. van; Boer, W.F. de (Wetlands ecology and management, 2009)
While mangrove restoration efforts are reasonably successful, failure often occurs in high wave energy situations. Due to differences in wave energy, seedling mortality rates vary strongly with position on the intertidal flat between high water spring and high water neap elevations. However, a local positive feedback can be present between the pneumatophores of adult mangroves and the survival of mangrove seedlings to trigger recovery. In this study, a mangrove population of Avicennia marina is modelled to determine the effects of seedling mortality and local positive feedback on mangrove recovery. The model uses life history data and dispersal to simulate population dynamics. The mangrove range limits are determined by high water spring and high water neap levels. The results indicate that within these limits mangrove populations with life-history parameter values as derived from literature are indeed capable of fast growth under conditions with low seedling mortality. Local positive feedback has then a small positive influence on population recovery after mangrove loss. If, however, mortality rates increase, such as in high wave energy situations, the importance of a positive feedback increases. The model shows that a positive feedback may, given high seedling mortality rates, be an important factor for mangrove recovery. While a positive feedback may enable mangrove persistence in unfavourable conditions, destruction of adult mangroves can remove the positive feedback, which would render the system uninhabitable and practically prohibits reforestation of such areas. The model results and the presence of positive feedbacks and their importance for population dynamics in harsh conditions indicate that investigating and understanding possible feedbacks could be crucial for successful restoration efforts.